The effect of the COVID-19 pandemic on riding lesson barns and summer camps in Ontario - Merkies, K.; Copelin, C.; Crouchman, E.; St-Onge, A. (Animals, 2020)
Simple Summary: Many riding lesson facilities are experiencing financial hardship due to COVID-19 pandemic restrictions that forced them to cease public-facing activities in March 2020. With the easing of restrictions in June 2020, riding lesson facilities were once again able to offer riding lessons and summer camps with modified protocols. Seventy-two riding facilities responded to an online survey to detail their operating protocols and the effect of these restrictions on their programs. Most facilities reported a decrease in the number of lessons they offered and the number of students per lesson. Less than half of the respondents offered summer camp programs. Both riding lessons and camp programs limited access to certain spaces in their barn or on their farm, and disinfected high contact areas and tack. Facemasks were not used by many facilities, however recent evidence suggests that facemasks should be worn even for outside activities. Despite the pandemic instigating challenges and hardships for many, there were nevertheless positive outcomes mentioned by many survey respondents. These included more time to spend with the horses, to attend to maintenance and repairs around the farm, more respect for barn rules and re-evaluation of business procedures and financial viability. Abstract: The COVID-19 pandemic has direct effects on the operations of riding lesson facilities and summer camps, with little government guidance on how to implement these. An online survey link was distributed to riding lesson facilities in Ontario. Descriptive statistics of respondents (n = 72) reported a decrease in both the number of riding lessons offered and the number of riding students per lesson. Scheduling riding times and limiting access to specific places on the farm ensured controlled access to the farms. Strict hygiene procedures were implemented including disinfecting high contact areas and shared tack. Summer camps followed the same procedures, although some farms chose not to offer camps at all. The use of facemasks was not prevalent in either riding lessons (43.3%) or camps (25%), likely because the activities took place outside. However, recent evidence shows that facemasks are perhaps even more important when outdoors, and it is recommended that riding lesson facilities re-evaluate their requirements for students and staff to wear facemasks while in the barn. In spite of the hardships, many positive aspects were noted including time to attend to repair and maintenance needs, scrutinizing business practices, more respect for barn rules, and more time to bond with the horses.